EFEKTIVITAS SERUAN AKSI BOIKOT PRODUK PRO ISRAEL TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA BAGI PRODUK LOKAL - Kurniawan, Rony Setyo; Juhari, Juhari; Zufriady, Zufriady; Holanda, Sella (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
The dispute between Israel and Palestine is one of the longest and most complex armed conflicts in the history of the modern world. This study aims to explore and analyze the effectiveness of the call for boycott action against pro-Israel products and their affiliates in the context of consumer purchasing decisions and their impact on local products. The research method used is qualitative, with a focus on observation and literacy studies. A literature study was conducted on data from social media and other sources related to the call for a boycott. The findings of this study highlight that the call for boycott action has a significant impact on consumer purchasing decisions. The motivation of consumers to engage in the boycott involves ideological, ethical, and solidarity factors with the Palestinian people. Local products benefit from positive perceptions related to support for the boycott movement, but are also faced with challenges, such as the need to maintain product quality and manage political tensions. The impact of the threat of a wave of termination of employment must be a concern by the Government due to the boycott if it is carried out continuously. The study provides an in-depth understanding of the complex dynamics between boycott calls, consumer purchasing decisions, and their impact on local products. The implications of these findings can help producers, stakeholders, and policymakers develop strategies that are responsive to global political issues and changing market dynamics